2022
DOI: 10.3390/cancers14020341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stereotactic Radiosurgery in the Management of Foramen Magnum Meningiomas—A Multicenter Analysis and Review of the Literature

Abstract: Background: Foramen magnum meningiomas (FMMs) represent a considerable neurosurgical challenge given their location and potential morbidity. Stereotactic radiosurgery (SRS) is an established non-invasive treatment modality for various benign and malignant brain tumors. However, reports on single-session or multisession SRS for the management and treatment of FMMs are exceedingly rare. We report the largest FMM SRS series to date and describe our multicenter treatment experience utilizing robotic radiosurgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In one study, 3 these patients were administered a median marginal dose of 20.0 Gy in 5 sessions and a median maximum dose of 45.0 Gy, at a median isodose line of 45%. In the other study, 9 these patients were administered a median marginal dose of 21.0 Gy in 3-5 sessions, and tumor volumes were significantly larger (median volume 5.3 vs 2.1 cm 3 ; p < 0.01) than those in patients undergoing singlefraction treatment.…”
Section: Summary and Description Of Treatment (Srs) Characteristicsmentioning
confidence: 89%
See 4 more Smart Citations
“…In one study, 3 these patients were administered a median marginal dose of 20.0 Gy in 5 sessions and a median maximum dose of 45.0 Gy, at a median isodose line of 45%. In the other study, 9 these patients were administered a median marginal dose of 21.0 Gy in 3-5 sessions, and tumor volumes were significantly larger (median volume 5.3 vs 2.1 cm 3 ; p < 0.01) than those in patients undergoing singlefraction treatment.…”
Section: Summary and Description Of Treatment (Srs) Characteristicsmentioning
confidence: 89%
“…The weighted median time to regression was 18 months from 3 studies 3,19 (including ours) with available data. The 3 largest studies calculated PFS rates and reported 5-year PFS rates of 100%, 3 93%, 9 and 92%. 19 PFS at 10 years remained at 100% 3 and 92% 19 in the 2 studies with available data.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations